1993
DOI: 10.1111/j.1348-0421.1993.tb03211.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the rfbT Gene Are Responsible for the Ogawa to Inaba Serotype Conversion in Vibrio cholerae O1

Abstract: In cultures of Vibrio cholerae strains of Ogawa serotype, variant strains which had undergone serotype conversion from Ogawa to Inaba were identified. The rfbT genes cloned from the parent strains were found to produce a 31-kDa protein in the maxicell system, and to cause serotype conversion when introduced into E. coli cells expressing Inaba serotype specificity. On the other hand, rfbT genes cloned from the variant strains neither produced the 31-kDa protein nor caused serotype conversion. Nucleotide sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…It has been suggested that serotype switches are the result of selective pressure on the organism due to the acquisition of immunity. This was shown in previous work by Stroeher et al (1992), and has been borne out by others (Ito et al, 1993;Wachsmuth et al, 1993;Garg et al, 2000).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…It has been suggested that serotype switches are the result of selective pressure on the organism due to the acquisition of immunity. This was shown in previous work by Stroeher et al (1992), and has been borne out by others (Ito et al, 1993;Wachsmuth et al, 1993;Garg et al, 2000).…”
Section: Discussionsupporting
confidence: 74%
“…Other strains also showed point mutations within the wbeT gene that did not affect serotyping (Ito et al, 1993). Three further strains, two isolated from Mpumalanga (S69145/80 and S69175/80) and one from KwaZulu-Natal (K1290/01) (neighbouring provinces in South Africa), showed the same amino acid changes at position 157-160 (Fig.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Further subcloning experiments (11,25) showed that the gene designated rfbT, encoding a protein of 33 kDa, is responsible for the expression of the Ogawa 0-form specificity. Ito et al (13) reported that mutations in the rfbT gene resulted in disappearance of the ability to produce the full-length protein of 33 kDa and consequently caused the conversion of the serotype from Ogawa to Inaba. In the present study, LPS was isolated from strains of E. coli K12 in which cosmid clones derived from V cholerae 01 NIH 41 (Ogawa) and NIH 35A3 (Inaba) had been introduced.…”
mentioning
confidence: 99%